ANALYSIS OF MODERN TRENDS AND OPPORTUNITIES IN THE LOGISTICS CHANNELS OF ENERGY PRODUCTS PRODUCERS - Olexander Generalov (Baltic Journal of Economic Studies, 2024)
The purpose of the article is to highlight the crucial role of logistics in ensuring efficient, sustainable and reliable energy distribution, especially in the face of challenges posed by global events such as Russia's invasion of Ukraine and the ongoing energy crisis. The dynamics of logistics channels in the energy sector are undergoing significant transformation due to technological innovations, geopolitical developments, environmental considerations and changes in energy sources. This study examines the current trends and opportunities in the logistics channels of energy producers, with a particular focus on how these elements are affecting the logistics landscape of the energy market. Methodology. The methodological approach combines a comprehensive review of current literature, analysis of industry reports and case studies to assess the evolution of logistics practices in the energy sector. According to the study, the logistics framework of the energy sector is changing as a result of a strong push for sustainability and technological advancement, which is driving the need for creative logistics solutions. Efforts to promote environmental sustainability are driving green logistics, and digitalisation is increasing operational efficiency across the supply chain. Results. The article emphasises the importance of sustainable and diversified clean energy supply chains, and stresses the need for strategic international cooperation to overcome the complexities of the current global energy landscape. The practical implications of this study suggest that stakeholders in the energy sector, including policy makers, businesses and researchers, need to adapt to these new trends to promote a more sustainable, efficient and responsive logistics infrastructure. The value/originality of this research lies in the comprehensive analysis of the factors driving changes in energy product logistics, offering insights into the strategic directions for the development of sustainable energy supply chains in the face of ever-changing global challenges.